Love streams - Harwood, Bo ca. 20. Jh (<<The>> Criterion Collection, 2014)
"The electric filmmaking genius John Cassavetes and his brilliant wife and collaborator Gena Rowlands give luminous, fragile performances as two closely bound, emotionally wounded souls who reunite after years apart. Exhilarating and risky, mixing sober realism with surreal flourishes, "Love streams" is a remarkable film that comes at the viewer in a torrent of beautiful, erratic feeling. This inquiry into the nature of love in all its forms was Cassavetes's last truly personal work." [criterion]
Aspect ratio 1.85:1. - New 2K digital restoration
Orig.: USA 1984
Enth. new audio commentary featuring writer Michael Ventura ; new video essay on actor Gena Rowlands by film critic Sheila O'Malley ; new interviews with executive producer and director of photography Al Ruban and actor Diahnne Abbott ; interview from 2008 with actor Seymour Cassel ; "I'm almost not crazy ..." - John Cassavetes: the man and his work (1984), a sixty-minute documentary by Ventura on the making of "Love streams" ; trailer ; an essay by critic Dennis Lim